PEMBUATAN SET EKSPERIMEN GERAK JATUH BEBAS BERBASIS MIKROKONTROLER DENGAN TAMPILAN PC - Dasriyani, Yohanna; Hufri, Hufri; Yohandri, Yohandri (Sainstek : Jurnal Sains dan Teknologi, 2014)
Experiment of free fall motion is one of phenomena in physic. Parameters of free fall motion still measured by stopwatch and meter. The purpose of research is development of free fall motion experiment set based on microcontroller with personal computer display. This instrument have highest precision and accuration. Average of measured result is 9,821 ± 0,025 with average of precicion relative is 98,3% and average accuration is 0,992.Key words: free fall motion, microcontroller, pc